Optimization of the working regime of the active medium in transmitters of the laser-location stations during the AES observations - Lyubich, I. V. (Одеські астрономічні публікації, 2017)
The necessity of the use of impulses of asymmetrical form is grounded with the purpose of providing of the most acceptable mode of operations of impulsive lamp. Power efficiency of active body of laser is investigational at influence of "double" impulses of pumping.